If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + -2x = x + -8 Reorder the terms: 10 + -2x = -8 + x Solving 10 + -2x = -8 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 10 + -2x + -1x = -8 + x + -1x Combine like terms: -2x + -1x = -3x 10 + -3x = -8 + x + -1x Combine like terms: x + -1x = 0 10 + -3x = -8 + 0 10 + -3x = -8 Add '-10' to each side of the equation. 10 + -10 + -3x = -8 + -10 Combine like terms: 10 + -10 = 0 0 + -3x = -8 + -10 -3x = -8 + -10 Combine like terms: -8 + -10 = -18 -3x = -18 Divide each side by '-3'. x = 6 Simplifying x = 6
| .07(5t-3)=.35(t+5)-1.96 | | 5d+4d+3d-4=2d | | 4(9p+6)+3p= | | 4x^2+17x+2ifx=10 | | 6x+1=18x-29 | | 3(6+x)=54 | | 4c+2c+5c=11c | | 5(7-2a)= | | -6(-5n+4)=38-n | | -5(5p+4)-30=2(3p+6) | | (8+y)(3+y)=0 | | .4(a+20)=6 | | 3x-4(3x+3)=60 | | 3(3-5x)= | | 3x(4x+40)=360 | | x^2*x^4=15625 | | 62=-2(-1-2t) | | (8c^4-1)(2c^4-4)= | | 5x=-2-13 | | 34p=45p+32 | | 6(v-4)-2=-7(-4v+2)-4v | | 7x+40=360 | | 8(10-5p)= | | 2+9n=4n+7 | | -6x+2(x+8)=-24 | | 6(z-2)+5z-2= | | 5(x+4)=-2x-8 | | 8y+3(y-5)=6(y+1)-2 | | 3(c-5)+5=2+c-12 | | 3(1-10x)= | | -8(2-7p)=-16-8p | | 90-9x=-70-x |